Dinamika Lingkungan Kerja Dan Implikasinya Terhadap Kinerja Guru Pendidik - Bella Kurnia Sari Sintha; Muhammad Ali Aqsa (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This research was conducted at Telkom Pekanbaru Vocational School. This research aims to determine the influence of the work environment on the performance of permanent foundation teachers at Telkom Pekanbaru Vocational School. The population in this study was 68 teachers. The sample in this study was taken based on the saturated sampling method. The sample in this research was 68 teachers. In analyzing the data obtained from this research the author used descriptive analysis and quantitative analysis methods. From the results of research using descriptive analysis, it was stated that the respondents' responses to the Work Environment variable were agree and the Teacher Performance variable was agree. Based on the results of research using quantitative analysis, it is known that the work environment has a positive and significant effect on teacher performance as evidenced by the simple linear regression equation Y = 1.578 + 0.700 significant level 0.000 < 0.05. From the determination test it is known that (R2) is 0.543. Which means that the Work Environment variable has an influence of 54.3% on Teacher Performance at Telkom Pekanbaru Vocational School, the remaining 45.7% is influenced by variable factors that were not studied.